The Influence of Character Building and Parents Economic Conditions on Student Learning Achievement - Lase, Juni Berkat Arman Jaya; Lahagu , Arianto; Harefa , Yearning; Lase, Asali (Manunggal Halim Jaya, 2024)
Based on the observations, it was found that a significant number of eighth-grade students at SMP Negeri 1 Alasa demonstrate low academic achievement, as evidenced by their test scores not meeting the Minimum Competency Criteria (KKM). Additionally, many students in this grade frequently fail to complete homework and exhibit a lack of motivation during the learning process. This study aims to analyze the influence of Character building and parental economic conditions on the academic performance of eighth-grade students at SMP Negeri 1 Alasa in 2024. The research employed a quantitative methodology. The findings indicate that Character building, in isolation, has a significant impact on the academic performance of eighth-grade students at SMP Negeri 1 Alasa, with a t-value of 2.231, which exceeds the critical t-value of 1.673. On the other hand, parental economic conditions do not have a significant effect on students' academic achievement when considered independently. This is evidenced by a t-value of -0.084, which is below the critical t-value of 1.673. Thus, students can achieve academic success regardless of their parents' lower economic status, and wealthier parents do not necessarily guarantee improved academic performance in their children.